Ways of seeing Malaysia women: sketches of women in megazines in the global age - Wang, Lay Kim (2007)
It has been argued that popular women‟s magazines can help to advance the cause of progressive movements by providing feminist views in mainstream magazines. It is with this in mind that an analysis of local magazines is done to see what sketches local magazines produce of women, women‟s issues and the women‟s movement struggles for greater equality and emancipation. Would feminist issues be visible in magazines here just as has been argued for magazines in the west? From the analysis of four top magazines in Malaysia namely Jelita, Wanita, Feminin & Famili and Remaja, it was found that these magazines are generally not known for their radical thoughts nor are they repository for feminist thinking. There is no denying that some articles may have picked up feminist issues whether deliberately or accidentally, but the focus is on how self can be transformed rather than on social transformation. This article suggests that existing mainstream media need continuous monitoring of biases to push the boundaries of coverage of women‟s concerns and perspectives. If a feminist perspective is to be realized, a greater voice is needed not only in the political process but also in the media.